Structural Development and Establishment of Rampt Models in Roadside, Farmland and Other Slopel and Agroforestry - Hossain, MA (Progressive Agriculture, 2014)
The three different models of Roadside Agroforest Multistoried Production Technologies (RAMPT) have been established at Bangladesh Agricultural University Campus, Mymensingh, Bangladesh. These are RAMPT-1 : Single Step Single Slope RAMPT [(SS)2 RAMPT], RAMPT-2 : Double Steps Double Slopes RAMPT [(DS)2 RAMPT], and RAMPT-3 : Triple Steps Triple Slopes RAMPT [(TS)2 RAMPT]. The results of on-going experiments both on MPTS and herbaceous species including crops and medicinal plants under the above models have been observed to be effective and encouraging with a 100% success in tree plantation. Neem, Mehogani and Bakphul based multistoried production systems have been established with understoried shrubby and herbaceous species like Jatropha, lemon, Eryngium, sunflower, turmeric, stem amaranth, chilli, ladys finger (okra), sweet gourd, etc. The structural development and establishment of these models have been described. DOI: http://dx.doi.org/10.3329/pa.v18i2.18165 Progress. Agric. 18(2): 99 - 107, 2007